2020
DOI: 10.1182/bloodadvances.2020001726
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine-induced immune hemolytic anemia: a case report and systematic review of the literature

Abstract: Key Points Bendamustine can cause severe autoimmune hemolytic anemia (AIHA), which may require plasma exchange and aggressive immunosuppression. Bendamustine-induced AIHA can be delayed, and many, but not all, cases report prior exposure to fludarabine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Therefore, treatment with 6 cycles of rituximab + cyclophosphamide and dexamethasone (R 375 mg/m², C 750 mg/m², dexamethasone 12 mg absolute 5 days; R-CD) was chosen as first line therapy with the rationale to have a substantial effect on both conditions. 29,30 As a result, his blood count returned to near normal values with WBC 7 x10 9 /L, hemoglobin 12.4 g/dL and platelets 107 x10 9 /L. This case shows the efficacy of both, steroid monotherapy as well as Rituximab combination therapy (against both CLL and ITP).…”
Section: Immune Thrombocytopeniamentioning
confidence: 74%
“…Therefore, treatment with 6 cycles of rituximab + cyclophosphamide and dexamethasone (R 375 mg/m², C 750 mg/m², dexamethasone 12 mg absolute 5 days; R-CD) was chosen as first line therapy with the rationale to have a substantial effect on both conditions. 29,30 As a result, his blood count returned to near normal values with WBC 7 x10 9 /L, hemoglobin 12.4 g/dL and platelets 107 x10 9 /L. This case shows the efficacy of both, steroid monotherapy as well as Rituximab combination therapy (against both CLL and ITP).…”
Section: Immune Thrombocytopeniamentioning
confidence: 74%
“…Rituximab, azathioprine, cyclophosphamide, cyclosporine, danazol, mycophenolate, and IV immunoglobulin are considered effective in the treatment of severe or refractory autoimmune haemolytic anaemia (23,33), but their efficacy in the treatment of DIIHA remains unclear (8). It has been reported that the administration of TPE to patients with severe DIIHA and renal impairment can be effective (8). Our patient experienced recurring haemolytic anaemias associated with cefoperazonetazobactam or cefoperazone-sulbactam, due to delay in diagnosis.…”
Section: Discussionmentioning
confidence: 88%
“…It is very important to discontinue the administration of the related drugs in time and provide the right targeted treatment (31). Corticosteroids are widely used in the treatment of DIIHA, but their effectiveness is difficult to be distinguished from the benefits of stopping the use of the causative drug (8,32). Rituximab, azathioprine, cyclophosphamide, cyclosporine, danazol, mycophenolate, and IV immunoglobulin are considered effective in the treatment of severe or refractory autoimmune haemolytic anaemia (23,33), but their efficacy in the treatment of DIIHA remains unclear (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 140 drugs are associated with drug-induced immune hemolytic anemia (DIIHA) (1)(2)(3)(4)(5)(6)(7)(8)(9). The pathogenic mechanism of DIIHA involves the damage of red blood cells (RBCs) by drug-induced (drug-dependent and -independent) antibodies or non-immune protein adsorption (NIPA) (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%